The Importance and Necessity of Liberalization of The Uzbekistan Economy (Zien Journal of Social Sciences and Humanities, 2022)
This article describes the essence of economic liberalization, theoretical and practical measures to ensure economic freedom in a market economy, the strategy of developed countries in liberalization and the stages of introduction of economic liberalization in Uzbekistan today, the pros and cons.